A HIGH GRADE DIFFUSE B CELL LYMPHOMA PRESENTED WITH ISOLATED LARGE SPACE OCCUPYING LESION IN THE FRONTAL LOBE MIMICKING HIGH GRADE GLIOMA OR FUNGAL GRANULOMA CASE REPORT AND REVIEW OF LITERATURE - Saeed Mazher; Abdul Ali (Journal of University Medical & Dental College, 2015)
ABSTRACTPrimary high grade B-cell-type cerebral lymphoma is a rare subtype of primary central nervous system lymphoma. We herein report an unusual case of diffuse B-cell lymphoma in a young lady who presented with a large intracerebral space occupying lesion without extracranial involvement. The notable aspects of this case include the patient was having a short clinical history of symptom onset, rapid neurological deterioration having severe midline shift on imaging and a ﬁnal histopathological diagnosis was consistent with high-grade diffuse B cell lymphoma after subtotal surgical resection. Extracranial extension of the disease was unremarkable on PET scanning. This case highlights the challenges neurosurgeons face, especially in the emergency setting, when the disease manifests in varied presentations.